Peningkatan Kreativitas Dan Imajinasi Anak Usia Dini Melalui Media Loose Part Berbahan Alam Di Kelompok A RA Tanjung Assalam - Jubaedah, Endah; Sadiyah, Siti Halimah (LP2M STAI Al-Musaddadiyah Garut, 2024)
This research is motivated by problems in group A at RA Tanjung Assalam Pakenjeng for the 2022/2023 Academic Year, including the lack of interest in learning in class children due to several factors such as learning media, lack of children's creativity in developing existing media. Teachers only use traditional methods and conventional media. So we need a solution of some of these problems. Loose part media made from nature can be used as an alternative media that can increase children's creativity and imagination. The purpose of this research is to increase creativity and imagination in group A through loose part media made from natural materials. The type of research is (PTK) with the Kemmis MC and Taggart models, the method used is a qualitative approach and data collection is taken in cycle I and cycle II with data collection techniques including observation, interviews and documentation. Based on the results of the research in the pre-cycle the ability to recognize natural materials developed according to expectations and developed very well 12% then after being carried out or applied loose part media the children's creativity increased from a total of 24 students in cycle I developed according to expectations and grew very well reaching 58% and at the end of Cycle II of the 24 students who developed according to expectations and developed very well reaching 96%. Keywords: Creativity and imagination, loose parts made from nature